Translation and Psychometric Evaluation of the Chinese Version of Functional Digestive Disorders Quality of Life Questionnaire - Feng-bin, Liu (Springer US, 2013)
BACKGROUND: Few useful patient-reported outcomes scales for functional dyspepsia exist in China. AIMS: The purpose of this work was to translate and cross-culturally adapt the Functional Digestive Disorders Quality of Life Questionnaire (FDDQL) from the English version to Chinese (in Mandarin). METHODS: The following steps were performed: forward translations, synthesis of the translations, backward translations, pre-testing and field testing of FDDQL. Reliability, validity, responsiveness, confirmatory factor analysis, item response theory and differential item functioning of the scale were analyzed. RESULTS: A total of 300 functional dyspepsia patients and 100 healthy people were included. The total Cronbach’s alpha was 0.932, and split-half reliability coefficient was 0.823 with all test–retest coefficients greater than 0.9 except Coping With Disease domain. In construct validity analysis, every item correlated higher with its own domain than others. The comparative fit index of FDDQL was 0.902 and root mean square error of approximation was 0.076. Functional dyspepsia patients and healthy people had significant differences in all domains. After treatment, all domains had significant improvements except diet. Item response theory analysis showed the Person separation index of 0.920 and the threshold estimator of items was normally distributed with a mean of 0 and standard deviation of 1.27. The residuals of each item were between −2.5 and 2.5, without statistical significance. Differential item functioning analysis found that items had neither uniform nor non-uniform differential item functioning in different genders and age groups. CONCLUSIONS: The Chinese version of FDDQL has good psychometric properties and is suitable for measuring the health status of Chinese patients with functional dyspepsia.